Sturm type oscillation theorems for equations with block-triangular matrix coefficients - Rofe-Beketov, F. S.; Kholkin, A. M. (Methods of Functional Analysis and Topology, 2012)
A relation is established between spectral and oscillation properties of the problem on a finite interval and a semi-axis for second order differential equations with block-triangular matrix coefficients.